2001
DOI: 10.1523/jneurosci.21-20-08222.2001
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Direction of Fingertip Forces by Human Tactile Afferents

Abstract: In most manipulations, we use our fingertips to apply time-varying forces to the target object in controlled directions. Here we used microneurography to assess how single tactile afferents encode the direction of fingertip forces at magnitudes, rates, and directions comparable to those arising in everyday manipulations. Using a flat stimulus surface, we applied forces to a standard site on the fingertip while recording impulse activity in 196 tactile afferents with receptive fields distributed over the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
211
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(226 citation statements)
references
References 72 publications
12
211
0
3
Order By: Relevance
“…Mechanical stimuli were delivered to the tip of the receptor-bearing finger (i.e., right index, middle, or ring finger) using a custom-built computer-controlled stimulator that allowed control of force or position in three dimensions. A previous report describes in detail the apparatus used to deliver the mechanical stimuli (Birznieks et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical stimuli were delivered to the tip of the receptor-bearing finger (i.e., right index, middle, or ring finger) using a custom-built computer-controlled stimulator that allowed control of force or position in three dimensions. A previous report describes in detail the apparatus used to deliver the mechanical stimuli (Birznieks et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Given their abundance, in the present study we asked whether the SA-IInail afferents might contribute important information about mechanical events at volar skin areas of the fingertips that directly contact objects during natural use of the digits. Because widespread complex stresses and strains occur all over the fingertip when it deforms in response to forces applied on objects, tactile afferents not only in the skin area contacting an object, but also at the end and sides of the fingertip, can convey information about contact forces (Bisley et al, 2000;Birznieks et al, 2001;Jenmalm et al, 2003;Johansson and Birznieks, 2004). We hypothesized that also SA-IInail afferents might encode fingertip forces because of significant changes of the tension in collagenous fiber strands of the paronychium where their end organs are situated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when judging stickiness, subjects do not substantially vary the normal forces they apply on the surface, but the applied tangential forces tend to vary across surfaces, suggesting that tangential forces are critical in the perception of stickiness (Smith and Scott 1996). As SA2 fibers are sensitive to skin stretch (Witt and Hensel 1959;Iggo 1966;Knibestöl 1975), this population of mechanoreceptive afferent fibers may provide the peripheral signals underlying stickiness perception, although recent evidence suggests that other mechanoreceptive afferents also convey information about forces exerted on the skin (Birznieks et al 2001). Vibratory cues may also be a factor in the perception of stickiness: as the skin skitters across a sticky surface, vibrations are produced in the skin (likely transduced and processed within the Pacinian system) which may contribute to the perception of stickiness (Bensmaia and Hollins 2005).…”
Section: Neural Mechanisms Of Texture Perceptionmentioning
confidence: 99%
“…Lashley [22] argued that, in the rapid sequences of articulation, sensory control is unlikely to play a role; rapid sequences of course also occur in music. It is of interest, however, that single tactile afferents may encode delicate fingertip forces, as demonstrated by Birzniek et al [5]. Furthermore, it was concluded that, during speech, b. .…”
Section: Feedforward and Feedback In Motor Control Of Music Performancementioning
confidence: 98%